Study on the coordination and factors affecting the coupling of resource and environmental carrying capacity and regional economy in ecologically fragile areas - Wang, Xiaomin; Bu, Xiaoyan; Wang, Jiarui; Du, Lingna; Hong, Zhichang; Shi, Ge; Baqiatullah (Ecological indicators, 2024)
•The RECC integrated model based on the SDGs and ecological civilization.•From 2010 to 2021, the RECC is on an upward trend in Ningxia.•In 2021, water, forest, and grassland resources are in a state of overload in Ningxia.•The coupling coordination has increased between RECC and regional economy in Ningxia.•Providing reference for the construction of world ecological civilization. The coordinated development of the resources, environment and social economy in ecologically fragile areas has become one of the urgent issues for all countries in the world. In this study, the ecologically fragile area of Ningxia was used as the typical case area. This study constructs a “four main subjects and eight dimensions” comprehensive evaluation model based on the Sustainable Development Goals (SDGs) to analyze the situation of the resource and environmental carrying capacity (RECC). This study employs the coupled coordination degree model and the obstacle degree model, integrating them with Pearson correlation analysis to quantitatively evaluate the coupled coordination relationship and influencing factors between RECC and socioeconomic development in Ningxia. The study shows that: (a) the RECC in Ningxia is on an upward trend, with obvious spatial differences, and the pressure on resources and environment in the provincial capital city is more obvious; (b) the coordination of RECC and socioeconomic development coupling in Ningxia is on a steady upward trend, but the internal development differences are more obvious, and the degree of coordination in the provincial capital cities is relatively high; (c) the coordinated development of RECC and socioeconomic development is affected by a combination of factors such as climate, water, soil, ecological resources, urbanization, and traffic accessibility in Ningxia. The findings offer scientific support for the coordination of socioeconomic development and resource environmental protection in ecologically fragile regions. Furthermore, they serve as a reference for promoting ecological civilization construction in fragile ecosystems globally.